2020
DOI: 10.3390/nano10010117
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Coated Magnetic Iron Oxide Nanoparticles Grafted onto Graphene Oxide for Protein Isolation

Abstract: In this study, silica-coated magnetic iron oxide nanoparticles (MNPs@SiO2) were covalently conjugated onto graphene oxide (GO/MNP@SiO2) for protein isolation. First, MNPs were precisely coated with a silica layer on the surface by using the reverse microemulsion method, followed by incubation with 3-glycidyloxypropyltrimethoxysilane (GPTS) to produce the GPTS-functionalized MNPs@SiO2 (GPTS-coated MNPs@SiO2) that display epoxy groups on the surface. The silica shell on the MNPs was optimized at 300 µL of Igepal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…In the last two decades, the great potential of superparamagnetic iron oxide nanoparticles (SPIONs) with their remarkable chemical and physical properties, such as nanoscale structure, magnetic characteristics, relative chemical stability, and biological compatibility, has been proved for nanomedicine applications [ 10 ]. SPIONs are of great importance for researchers in a wide range of applications including for cancer therapy, biotechnology, and drug delivery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, the great potential of superparamagnetic iron oxide nanoparticles (SPIONs) with their remarkable chemical and physical properties, such as nanoscale structure, magnetic characteristics, relative chemical stability, and biological compatibility, has been proved for nanomedicine applications [ 10 ]. SPIONs are of great importance for researchers in a wide range of applications including for cancer therapy, biotechnology, and drug delivery [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the silica shell thickness ranged from effectively zero to ca. 52 nm, in the latter case accompanied by the formation of bare silica nanoparticles, when the TEOS concentration was varied from 0.01 to 0.5 M [ 53 ]. EDX confirmed the average elemental composition of the MNPs and Sc-MNPs ( Supplementary Materials, Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most useful procedures for preparing heterogeneous nanocatalysts is to immobilize complexes on solid bases like metal and metal oxides. Magnetic iron oxide nanoparticles (MNPs Fe 3 O 4 ) have received a big deal of interest within metal oxide nanoparticles (NPs), probably because of their special applications [24][25][26]. Iron oxides have good magnetic properties compared to other magnetic nanoparticles and, on the other hand, show high stability against degradation [27,28].…”
Section: Introductionmentioning
confidence: 99%